2009
DOI: 10.1016/j.jaci.2009.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin mutations that confer risk of atopic dermatitis confer greater risk for eczema herpeticum

Abstract: Background Loss-of-function null mutations R501X and 2282del4 in the skin barrier gene, filaggrin (FLG), represent the most replicated genetic risk factors for atopic dermatitis (AD). Associations have not been reported in African ancestry populations. Eczema herpeticum (ADEH) is a rare but serious complication of AD resulting from disseminated cutaneous HSV infections. Objective We aimed to determine whether FLG polymorphisms contribute to ADEH susceptibility. Methods Two common loss-of-function mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
169
0
9

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 222 publications
(189 citation statements)
references
References 31 publications
11
169
0
9
Order By: Relevance
“…It is up to now unclear, whether viral warts or mollusca contagiosa are likewise more prevalent in AD. However, large studies have shown that it will be possible to identify patients at risk to develop eczema herpeticum on the basis of clinical, immunological and genetic informations 60,61 .…”
Section: ) Complicationsmentioning
confidence: 99%
“…It is up to now unclear, whether viral warts or mollusca contagiosa are likewise more prevalent in AD. However, large studies have shown that it will be possible to identify patients at risk to develop eczema herpeticum on the basis of clinical, immunological and genetic informations 60,61 .…”
Section: ) Complicationsmentioning
confidence: 99%
“…49,50 Patients with AE have an increased susceptibility to both disseminated viral (eczema herpeticum) and bacterial skin infections, 51 and the risk of both is increased in FLG-deficient subjects. 52 Consistent with this, stress responses, namely type 1 interferonmediated anti-pathogenic deference, are overrepresented in the transcriptome of FLG-null and haplosufficient patients with AE, 12 and furthermore, type 1 interferon expression is increased in patients with eczema herpeticum. 53 Type 1 interferons are secreted after viral 54 or bacterial 55 infection and mediate both immunomodulatory responses and local cell-cycle regulation in part through activation of eIF2, 56 mTOR, and downstream p70-S6K/eIF4 signaling.…”
Section: Discussionmentioning
confidence: 63%
“…They can be simultaneously triggered causing immune response. [32,33] The relationship between filaggrin and TH2 inflammation are shown in Figure 2. The homozygous FLG mutant carriers without filaggrin expression have severe and persistent allergic early-onset AD.…”
Section: Dithranolmentioning
confidence: 99%